2003
DOI: 10.1038/sj.emboj.7600036
|View full text |Cite
|
Sign up to set email alerts
|

Nbp2 targets the Ptc1-type 2C Ser/Thr phosphatase to the HOG MAPK pathway

Abstract: The yeast high osmolarity glycerol (HOG) pathway signals via the Pbs2 MEK and the Hog1 MAPK, whose activity requires phosphorylation of Thr and Tyr in the activation loop. The Ptc1-type 2C Ser/Thr phosphatase (PP2C) inactivates Hog1 by dephosphorylating phospho-Thr, while the Ptp2 and Ptp3 protein tyrosine phosphatases dephosphorylate phospho-Tyr. In this work, we show that the SH3 domain-containing protein Nbp2 negatively regulates Hog1 by recruiting Ptc1 to the Pbs2-Hog1 complex. Consistent with this role, N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
86
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(89 citation statements)
references
References 51 publications
3
86
0
Order By: Relevance
“…Ptc1p functions with Nbp2p in several signaling pathways (Ohkuni et al, 2003b;Mapes and Ota, 2004;Du et al, 2006), and Nbp2p also regulates the distribution of the vacuole and cortical ER (Du et al, 2006). The ptc1⌬ and nbp2⌬ strains share the same phenotypes including a defect in vacuole inheritance and fragmented vacuoles (Du et al, 2006;Supplemental Figure S7).…”
Section: Ptc1 Is Required For the Proper Association Of The Vacuole Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Ptc1p functions with Nbp2p in several signaling pathways (Ohkuni et al, 2003b;Mapes and Ota, 2004;Du et al, 2006), and Nbp2p also regulates the distribution of the vacuole and cortical ER (Du et al, 2006). The ptc1⌬ and nbp2⌬ strains share the same phenotypes including a defect in vacuole inheritance and fragmented vacuoles (Du et al, 2006;Supplemental Figure S7).…”
Section: Ptc1 Is Required For the Proper Association Of The Vacuole Tmentioning
confidence: 99%
“…Activation of the HOG pathway is regulated by a mitogenactivated protein kinase (MAPK) cascade, which leads to the phosphorylation of the MAPK, Hog1p. Ptc1p, which is recruited to the MAPK kinase Pbs2p through interaction with Nbp2p, inactivates Hog1p by dephosphorylating it (Warmka et al, 2001;Mapes and Ota, 2004). Both Ptc1p and Nbp2p also regulate the cell wall integrity (CWI) MAPK pathway (Ohkuni et al, 2003b).…”
Section: Introductionmentioning
confidence: 99%
“…Both the large number of characteristic phenotypes and the specific changes in the transcriptomic profile (Gonzalez et al 2006) derived from deletion of the gene suggest that this phosphatase is involved in a large variety of cellular processes not shared by other Ptc family members. Early evidence indicated that Ptc1 was involved in the negative regulation of the high-osmolarity glycerol (HOG) pathway (Maeda et al 1993;Maeda et al 1994), and subsequent work demonstrated that Ptc1 could dephosphorylate the Hog1 MAPK in vitro and in vivo (Warmka et al 2001 interacts with the N-terminal domain of Nbp2, an SH3 domaincontaining protein that serves as an adaptor for the recruitment of Ptc1 to the Pbs2-Hog1 complex, and this interaction is necessary for Ptc1 to participate in the regulation of HOGmediated signaling (Uetz et al 2000;Ito et al 2001;Mapes and Ota 2004). Cells lacking Ptc1 display many phenotypes that cannot be explained by a Hog1-dependent role of this phosphatase.…”
mentioning
confidence: 99%
“…interacts with the N-terminal domain of Nbp2, an SH3 domaincontaining protein that serves as an adaptor for the recruitment of Ptc1 to the Pbs2-Hog1 complex, and this interaction is necessary for Ptc1 to participate in the regulation of HOGmediated signaling (Uetz et al 2000;Ito et al 2001;Mapes and Ota 2004).…”
mentioning
confidence: 99%
“…However, it is possible that the Ahk1-binding site in the N-terminal region is masked in Pbs2-FL by an N-terminal-C-terminal (N-C) interaction, unless, for example, Pbs2-FL interacts with another molecule. The N-terminal noncatalytic domain of Pbs2 contains binding sites for several other signaling components involved in the HOG pathway, including Ssk2/22 (21), Sho1 (19), Hog1 (40), and Nbp2 (48). To determine if the Ahk1 binding domain (Ahk1-BD) is different from these other binding sites, we tested HA-Ahk1 binding to several deletion fragments derived from the N-terminal region of Pbs2 (Fig.…”
Section: Role Of the Cytoplasmic Domain Of Hkr1 In The Hog Pathwaymentioning
confidence: 99%